2015
DOI: 10.1093/bioinformatics/btv527
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of development by epithelia, mesenchyme and their interactions: a unified model

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 30 publications
0
61
0
Order By: Relevance
“…At present Chaste (81) (83,84), further work is required to make progress in this area. In particular, the development of methodologies to interface models that include descriptions of cell shape, mechanics and biochemical signalling in different ways and on different scales, will be crucial.…”
Section: Model Choice and Implementationmentioning
confidence: 99%
“…At present Chaste (81) (83,84), further work is required to make progress in this area. In particular, the development of methodologies to interface models that include descriptions of cell shape, mechanics and biochemical signalling in different ways and on different scales, will be crucial.…”
Section: Model Choice and Implementationmentioning
confidence: 99%
“…The mathematical model used in this study, the SpiralMaker, is a modification of a general model of animal embryonic development, the EmbryoMaker (Marin-Riera et al, 2016), that allows us to implement each of the developmental rules studied in this article. [The EmbryoMaker software implementing the model is available for download (http://www.…”
Section: Methodsmentioning
confidence: 99%
“…Therein each cell is represented as a set of subcellular elements (spheric elastic volumes) in three-dimensional space. The physical interactions between the subcellular elements (hereafter nodes) allows each whole cell to display visco-elastic properties like those observed in real cells (Newman, 2005;Sandersius and Newman, 2008;Marin-Riera et al, 2016). Thus, nodes can adhere to one another ( preferentially to nodes from the same cell but also to nodes from other cells) but repel each other if they are too close (reiterating the physical fact that two cells can not occupy exactly the same position in space).…”
Section: Introductionmentioning
confidence: 98%
“…Isaac Salazar‐Ciudad (University of Helsinki) presented a theoretical approach to evodevo, beginning with the question: if you were to design a gene network from scratch, what would it look like? To build a general model of animal development, Salazar‐Ciudad computationally generated a variety of random developmental gene networks and produced the corresponding phenotypes in silico (Marin‐Riera, Brun‐Usan, Zimm, Välikangas, & Salazar‐Ciudad, ). He found that mutations tend to decrease the complexity of phenotypes, and that most gene networks produce morphologies that are highly sensitive to noise.…”
Section: Theory and Modeling Approaches To Evodevomentioning
confidence: 99%